DEPOSIT INTEREST RATE EFFECT OF TOTAL SAVINGS DEPOSITS AT ACEH’S GOVERNMENT BANKS - Banta Karollah (SI-MEN, 2014)
This study describes the effect of interest rates on deposits at Aceh’s government banks. The study aims to find empirical evidence, which supports the notion that interest rates affect the amount of the deposit. In this study, a sample is taken from a data rate of deposits and savings deposits at Aceh’s government banks from the year 2010-2013, which is documented in Bank Indonesia in Banda Aceh.This study uses data collection through secondary data, method of analysis used is a simple linear regression using SPSS 20.00 program for Windows.Based on the research that has been done by simple linear regression equation that for a period of 1 month deposit is Y '= 3170429,531-330.072,252X, that the interest rate yield regression coefficient with a negative slope means that the level of interest rates negatively affect the amount of deposits. For the 3-month deposit is Y '= 2738951,943 + 616256,480 X, that the interest rate yield regression coefficient with a positive slope means that the interest rate has positive influence on the amount of deposits, and deposits 6 months is Y' = 1449516,119 – 165248,465 X, that the interest rate yield regression coefficient with a negative slope means that the level of interest rates negatively affect the amount of deposits and for 12-month deposits Y '= 1331468.342 to 42386.550 X, that the interest rate yield regression coefficients with a negative slope means interest rates negatively affect the amount of deposits. It was concluded that the deposits within a period of 3 months to contribute positively and significantly influence the rate of the increase at Aceh’s government banks, which means the interest rate affects the amount of deposits. deposits within a period of 1 month and 6 months to contribute a significant negative effect of interest rates on deposits in total deposits at Aceh’s government banks, which means the interest rate does not affect the amount of deposits, as well as for the deposit period of 12 months give contribution and no significant negative effect between the interest rate on the amount of deposits at Aceh’s government banks, which means the interest rate does not provide a positive and significant effect of the interest rate to increase the amount of deposits.